Keragaman Serangga Penyerbuk dan Hubunganya dengan Warna Bunga pada Tanaman Pertanian di Lereng Utara Gunung Slamet, Jawa Tengah (Diversity of insect pollinators and its relationship with flowers colors on Agricultural Crops in the Northern slopes of ...) - Imam WIDHIONO; Eming SUDIANA (Universitas Jambi, 2015)
Reseach on insect pollinators diversity and abundance on eight cash crops wasconducted at Serang, Sub District Karangreja, Purbalingga, Central Java, during June to oktober2012. The aims of this research were to observethe diversity and abundance of insect pollinators ateight food crops and their relationship with flowers colours. Sampling of insect pollinators specieswas done using scane sampling and direct observation of insect stay at the flowers. Insect diversitywas calculated using ShannonÂ´s index, Simpsons index and, and Shannon Eveness. Species turnover was calculated using Jaccard index. the calculations was performed using BD Pro(McAleece, et al., 1997). Sevententh species of insect pollinators was identified. Wings bean wasvisited by 12 species of insect pollinators with highest diversity indeces (H=2.14, D=0.86, and E=0.86,) followed by cucumber (11 species) with diversity indeces (H=1.89, D=0.75, and E= 0.75,),and the lowest was strawberry with only visited by 7 species with diversity indeces(H=1.25,D=0.64, and E= 0.64,).The most abundance insect pollinator species was local honeybees ( A. Cerana), followed by stingless bees (Trigona sp) and the lowest was Ropalidia romandiwith consist only 2 individual.There is no corelation between flowers colors with either insectpollinators diversity or abundance.